Performance of Cryptococcal Antigen Lateral Flow Assay Using Saliva in Ugandans with CD4 ,<100 - Kwizera, Richard; Nguna, Joyce; Kiragga, Agnes; Nakavuma, Jesca; Rajasingham, Radha; Boulware, David R.; Meya, David B. (PloS one, 2014)
Cryptococcal meningitis can best be diagnosed by cerebrospinal fluid India ink microscopy, cryptococcal antigen detection, or culture. These require invasive lumbar punctures. The utility of cryptococcal antigen detection in saliva is unknown. We evaluated the diagnostic performance of the point-of-care cryptococcal antigen lateral flow assay (CrAg LFA) in saliva.We screened HIV-infected, antiretroviral therapy naïve persons with symptomatic meningitis (n = 130) and asymptomatic persons with CD4+<100 cells/µL entering into HIV care (n = 399) in Kampala, Uganda. The diagnostic performance of testing saliva was compared to serum/plasma cryptococcal antigen as the reference standard.The saliva lateral flow assay performance was overall more sensitive in symptomatic patients (88%) than in asymptomatic patients (27%). The specificity of saliva lateral flow assay was excellent at 97.8% in the symptomatic patients and 100% in asymptomatic patients. The degree of accuracy of saliva in diagnosing cryptococcosis and the level of agreement between the two sample types was better in symptomatic patients (C-statistic 92.9, κ-0.82) than in asymptomatic patients (C-statistic 63.5, κ-0.41). Persons with false negative salvia CrAg tests had lower levels of peripheral blood CrAg titers (P<0.001).There was poor diagnostic performance in testing saliva for cryptococcal antigen, particularly among asymptomatic persons screened for preemptive treatment of cryptococcosis.